Tolerância de variedades de cana-de-açúcar (Saccharum spp.) à toxidez por alumínio em solução - Oliveira, Mariane de Souza (2012)
The influence of toxic aluminum (Al) on root development and absorption of water and nutrients has been identified as a major cause of low productivity of many soils. The theoretical and experimental study on the tolerance of varieties of sugarcane to adverse conditions of extreme acidity and, especially, high Al saturation, is still inconclusive The objectives of this study were: to develop and propose an experimental protocol for the study tolerance of varieties of sugarcane to Al in solution and to study the sensitivity of nine varieties of sugarcane (RB928064, RB966928, RB937570, RB855156, RB855453, RB935744, RB867515, RB925345, SP813250) to Al stress solution through a series of analyzes: (a) review the allocation of the Al at the tip roots, (b) observation of the root apices and (c) root growth; identify the main changes in the root; identify the critical dose to the Al root growth and identify the most efficient method for the classification of varieties on the Al in solution. The experiment was conducted in laboratory conditions in a completely randomized design with three replications. After the germination period, the mini-stalks of sugarcane were acclimated in tanks with nutrient solution. After six days, the mini-cuttings were transferred to containers with nutrient solution and increasing doses of Al (0, 130, 380, 500, 800, 1000, 1400, 2000, 3000 and 4000 μmol L -¹), where they remained for six days and subsequently were removed for analyzes. The development of the experimental protocol was efficient for the evaluation of tolerance and its main factors were germination method, selecting the range of Al concentration in solution and the methods of tolerance assessment. The varieties differed in Al tolerance according to the analyzes. The main changes of the tip root were mucilage production, loss of epidermal cells of the root cap and its disintegration, and brown staining of root tips. The root elongation rate (TAR) depended on the interaction between variety and concentration of Al, and, for the varieties studied, the critical value ranged from 130 to 3000 μmol L-¹. The TAR method was considered more efficient to evaluate the tolerance of varieties of sugarcane to Al in solution and in accordance with this method the varieties were classified as tolerance in the following order: RB928064 > RB935744 > RB855453 = RB966928 > RB925345 = RB867515 > SP813250 > RB855156 > RB937570.